2007
DOI: 10.1177/0961203307077988
|View full text |Cite
|
Sign up to set email alerts
|

MTR 2756 A > G polymorphism is associated with the risk of systemic lupus erythematosus in the Polish population

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by overexpression of cytokines and T cell accessory molecules, which is due to a reduction of DNA regulatory region methylation in T cells. It has been shown that polymorphic variants of genes encoding key enzymes of folate and methionine metabolism may have an effect on DNA methylation. Therefore, in patients with SLE (n = 106) and controls (n = 141) we examined the distribution of polymorphisms of genes encoding methionine synthase (MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
3
14
1
Order By: Relevance
“…Our results contrast with a smaller Italian study reporting that SLE patients had a higher prevalence of the MTHFR 677TT genotype 18 . A Polish study found that frequencies of MTHFR 677C>T were not different between SLE patients and controls, but the authors found that the MTR 2756G allele was overrepresented in SLE patients 32 , which contrasts with our finding of lack of an association.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results contrast with a smaller Italian study reporting that SLE patients had a higher prevalence of the MTHFR 677TT genotype 18 . A Polish study found that frequencies of MTHFR 677C>T were not different between SLE patients and controls, but the authors found that the MTR 2756G allele was overrepresented in SLE patients 32 , which contrasts with our finding of lack of an association.…”
Section: Discussioncontrasting
confidence: 99%
“…RFX1, a transcription factor that affects DNA methylation and histone acetylation by recruiting the corepressors DNMT1 and histone deacetylase 1 to the promoters of methylation-sensitive genes, was reported to be decreased in SLE T cells (50). Gene polymorphisms of methionine synthase, which is located in chromosome 1q43, a region confirmed to confer risk for the development of SLE, have been linked to SLE (51). Binding of methyl binding domain proteins or methyl cytosine-binding proteins (MECPs) to demethylated promoter regions is known to represent an indirect gene-silencing mechanism by preventing the binding of transcription factors to the targeted gene promoter (52, 53).…”
Section: Discussionmentioning
confidence: 99%
“…Many genes that encode proteins involved in the immune system have been designated as candidate susceptibility genes [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%